Effect of entrepreneurial marketing on SMEs competitive performance in Lesotho - Osakpamwan E.D. Amadasun; Ashley T. Mutezo (The Southern African Journal of Entrepreneurship and Small Business Management)
Background: Entrepreneurial marketing (EM) is an important market strategic concept that small and medium-sized enterprise (SME) owners or managers adopt and practise to drive their enterprises to attain competitive financial performance. Records indicate that in the past 20 years limited studies have focussed on EM strategic challenges that the Basotho SMEs face in Lesotho.